Border effects in passenger air traffic - Henning Klodt (Kiel Institute for World Economics (IfW), 2003)
National borders substantially matter in passenger air traffic. Empirical estimates based upon a new data set on domestic and international departures from German airports indicate that the German border reduces air traffic activity by a factor of four to five. This result adds a further piece of evidence to the significance of border effects in various kinds of economic activity.
Keywords: R12; F20; F15; 330; gravity model; border effects; Geldpolitik; Schock; Internationale Kapitalmobilität; Konsumentenverhalten; Offene Volkswirtschaft; Theorie